Human-induced Pluripotent Stem Cell Potential for Schizophrenia Therapy: A Literature Review - Kusumadewi, Andrian Fajar; Adi, Winengku Basuki (Fakultas Kedokteran Universitas Brawijaya, 2025)
Schizophrenia is a severe and chronic mental disorder characterized by a neurodegenerative process. Currently, there has been no cure for schizophrenia. However, a newer significant potential for modeling and curing schizophrenia has been recognized in human-induced pluripotent stem cells (HiPSCs), which are obtained from adult somatic cell reprogramming. This study aimed to assess the potential of HiPSCs in schizophrenia by reviewing relevant scientific journals published in reputable databases such as Springer, Elsevier, Science Direct, Nature, and Pubmed, in the last 10 years. Research findings indicate that stem cells can help determine the effectiveness of antipsychotics and repair damaged neuronal cells in certain areas of the brain by transplanting programmed stem cells. The proliferative ability of neuronal cells in schizophrenia tends to decline, affecting their physiological neurogenesis. HiPSCs have the potential to return the neuronal function in schizophrenia, offering new hope in psychiatry.